Eficiência das companhias aéreas brasileiras: uma análise envoltória de dados - Mattielo, Anna Cecília [UNESP] (2013)
Studies about efficiency have gained dimension, in Brazil, since the early 90’s. Same decade that the Civil Aviation System suffers important changes in terms of regulations. Such transformations have echoed effects currently, with some significant trend for international standards. This paper focuses on one of the agents from the Brazilian Civil Aviation System, the airlines companies, which aimed on analyze and evaluate both passengers and cargo air transport, by using data envelopment analysis (DEA), during the period of 2005 to 2010. The yearbooks of ANAC, corresponding at the period from 2005 to 2010, were used as data base in this present study. The technique was applied to 14 companies, which through Stepwise process of variables validation was possible to compose a compact, but complete model, that could translate the reality of companies. This model was composed by one output, Total Income, and by four inputs, Total Costs, Total Domestic Passenger, Total Cargo and Total International Passengers. However, this approach has some flaws. Therefore in order to remedy it, it was required to apply the method Frontier Inverted, one of the alternatives proposed in the literature, which ensured an improvement in the context of efficiencies due to biggest discrimination of airlines. As a result of the DEA-BCC process, oriented by output, TAM 2005 was considered the most efficient company, however GOL and Webjet companies concentrated in 2007 their worst levels